Doctor’s Conscience Clause and Pregnancy Termination. The Case of Poland - Michalczuk-Wlizło Marta (Studies in Logic, Grammar and Rhetoric, 2024)
The obligation to make women’s rights to health services a reality rests with the state authorities. However, in Poland, women wishing to carry out a legal termination of pregnancy are often confronted with institutional abuse on the part of health care providers who deny women the possibility of carrying out the procedure because gynaecologists invoke the institution of the conscience clause. The aim of this article is to show the mutual normative complexity of the research problem, i.e. the possibility for a doctor to invoke the conscience clause in the case of a patient’s right to an abortion. The paper verifies the research hypothesis that in the field of the conscientious objection clause, systemic solutions are necessary, but not only consisting in specifying the legal provisions but also in enforcing the respect of the law by its addressees. The hypothesis is to be verified using the dogmatic method.